THE INFLUENCE OF PRICE, ELECTRONIC WORD OF MOUTH (E-WOM), AND BRAND IMAGE ON PURCHASING DECISIONS IN SHOPEE E-COMMERCE PLATFORM - Tasriastuti, Nurrohmi Ambar; Harminingtyas, Rudika; Widowati, Maduretno (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2024)
The development of e-commerce platforms in Indonesia has had a significant impact on product purchasing behavior among students. The ease of access and wide selection of products offered through online shopping sites such as Shopee, Tokopedia, Lazada, and others, have made e-commerce the main channel for students to make purchases. The Shopee site stands out as one of the leading online shopping platforms in Southeast Asia, being. The main objective of this research is to determine and evaluate the influence of price, electronic word-of-mouth (e-WOM), and brand image on the purchasing behavior of Shopee application users among STIE Pelita Nusantara Semarang students. A purposive sampling approach was used in data collection, with a total of 72 respondents participating in this investigation. Primary data analysis in this research was carried out through multiple regression analysis. The research results show that price, electronic word-of-mouth (e-WOM), and brand image have a positive and important influence, both individually and collectively, on the purchasing decisions of Shopee application users among STIE Pelita Nusantara students. Within the framework of this research, price emerges as the most influential factor influencing purchasing choices. The coefficient of determination (R²) shows that 70.4% of the variance in the dependent variable of purchasing decisions can be explained by three independent variables: price, Electronic Word Of Mouth (E-WOM), and brand image.